Analisis Pergeseran Penggunaan Bahasa Dearah dalam Komunikasi di Desa Simpang Kabupaten Seluma Provinsi Bengkulu - Andriani, Zelta; Khermarinah, Khermarinah; Sari, Wenny Aulia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to describe the forms of language use in society based on age domains, namely children, teenagers, and adults. The research method used by researchers is a qualitative research method. Based on data on the form of use of the Serawai language and Indonesian using data sources from the Simpang Village community, Seluma district, obtained using the listening method, namely the proficient listening technique, the proficient non-involving listening technique, the recording technique, and the note-taking technique, as well as the proficient or interview method. The results of the research show that the adult community, although able to use the Serawai language actively, shows the dominant use of Indonesian in the form of their language use. Even though teenagers are able to understand the Serawai language, they are not able to use the Serawai language actively, while children have great difficulty and are even no longer able to use the Serawai language. Another indication is the existence of the Indonesian language, which should have displaced the Serawai language by Indonesian. This can be seen from the form of language use of children who actively use Indonesian dominantly. In conclusion, the Serawai language, which is the common language of the Simpang village community, is experiencing a serious shift. Keywords: Communication, Society, Language Shift.